Radical Islamism Hazards in Issues of Safety of Nuclear Industry Facility Construction and Operation - Nedorubov, A. N.; Lobkovskaya, N. I. (Глобальная ядерная безопасность, 2022)
The paper discusses the hazards of construction and operation of nuclear power facilities in countries with a predominantly Muslim population that is ambiguous about the development of the nuclear industry in their countries. The analysis shows the issue manifestation of radical Islamism in the territories where nuclear facilities are located and makes it possible to single out the most significant and specific features of the stated problem.